Composite aerogel felt containing organic-inorganic hybrid hollow microspheres as well as preparation method and application of composite aerogel felt

Through the reaction of atmospheric drying process and phytic acid, combined with organic and inorganic hybrid hollow microspheres, the high cost and structural instability problems in the industrial production of SiO2 aerogels are solved, and composite aerogel felts with high thermal insulation performance and large-scale production are achieved.

CN119569415APending Publication Date: 2025-03-07INST OF CHEM CHINESE ACAD OF SCI

Patent Information

Application Number
CN202311147343.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The industrial production of existing SiO2 aerogels faces high investment costs, safety risks and instability in the microstructure of materials, resulting in insufficient thermal insulation performance and difficulty in large-scale production.

Method used

A composite aerogel felt containing organic and inorganic hybrid hollow microspheres was prepared by normal pressure drying. The silica sol reaction was participated in the silicon sol reaction, which promoted the formation of silicon-oxygen silicon bonds, and introduced organic and inorganic hybrid hollow microspheres into the material to maintain the microstructure of the aerogel.

Benefits of technology

It realizes the stable microstructure of the aerogel felt, without agglomeration, better thermal insulation performance, sufficient silicon source reaction, no need for multiple washing and replacement, and no powder loss, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569415A_ABST
    Figure CN119569415A_ABST
Patent Text Reader

Abstract

The invention discloses a composite aerogel felt containing organic-inorganic hybrid hollow microspheres as well as a preparation method and application of the composite aerogel felt. The method provided by the invention adopts a normal-pressure drying preparation process and comprises the following steps: adding a silicon source, a solvent and phytic acid into water, carrying out hydrolysis reaction, and then adjusting the pH value of a system to obtain a silica sol solution; adding organic and inorganic hybrid hollow microspheres into the silica sol solution, and stirring to obtain a sol solution containing the organic and inorganic hybrid hollow microspheres; and soaking a fiber felt in the sol solution containing the organic-inorganic hybrid hollow microspheres, standing, and drying to obtain the composite aerogel felt. The composite aerogel felt provided by the invention is more stable in structure, better in heat insulation performance, free of agglomeration, free of powder falling, free of repeated washing and replacement, simpler in process and more suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silica aerogel composite thermal insulation materials, and specifically relates to a composite aerogel felt containing organic-inorganic hybrid hollow microspheres and a normal pressure drying preparation method and application thereof. Background Art

[0002] SiO2 aerogel is a material with a nano-space network structure. It is a lightweight nano-solid material with the characteristics of ultra-low density, high porosity, high specific surface area and ultra-low thermal conductivity. It was mainly used in aerospace, military industry and national defense in the early days, and then gradually expanded to petrochemical, industry, construction, transportation, daily use and other fields.

[0003] The traditional preparation method of SiO2 aerogel is generally to prepare alcohol gel through sol-gel method, and then use supercritical fluid drying process to remove the solvent in the pores of alcohol gel to obtain SiO2 aerogel with complete network structure. However, the supercritical fluid drying process is complicated, the equipment is expensive, the investment cost is high, and the high pressure conditions required for the drying process have disadvantages such as high operating cost and safety hazards, making the industrial production of aerogel difficult.

[0004] In order to promote the industrial production of SiO2 aerogel and realize the practical application of a series of products, researchers have developed a low-cost, safety-hazard-free atmospheric drying preparation process for SiO2 aerogel, which is mainly carried out by acid-base catalysis of the sol system with ammonia, hydrochloric acid or acetic acid, and then soaking the felt to form a gel felt, and finally forming an aerogel felt by solvent replacement. However, it is difficult to maintain the microstructure of the aerogel in the process of rapid solvent volatilization, and it is easy to form a cluster structure, which affects the thermal conductivity of the aerogel felt material; and because the raw material ethyl orthosilicate is not completely reacted, it is necessary to repeatedly wash and replace the solvent, the process is cumbersome and complicated, which is not conducive to large-scale production, and the aerogel felt formed is also easy to fall off. In addition, patent CN116122042 A introduces carbon nanotube / activated carbon composite microspheres into the aerogel felt system, which is convenient for surface modification to reduce the powdering of the felt, but the material of the microspheres is mainly organic components, which are easy to carbonize during the use of high-temperature pipelines, which is not conducive to long-term stable use. Summary of the invention

[0005] The purpose of the present invention is to provide a composite aerogel felt containing organic-inorganic hybrid hollow microspheres and a preparation method thereof. The composite aerogel felt is prepared by a normal pressure drying process, which has the advantages of simple process and low cost. At the same time, the obtained aerogel felt has a stable microstructure, no agglomeration, better thermal insulation performance, sufficient silicon source reaction, no need for multiple washing and replacement, no powder loss, etc., and is more suitable for large-scale production.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a composite aerogel felt by drying at normal pressure, comprising the following steps:

[0008] S1, adding a silicon source, a solvent, and phytic acid into water for hydrolysis reaction, and then adjusting the pH of the system to obtain a silica sol solution;

[0009] S2, adding organic-inorganic hybrid hollow microspheres to the silica sol solution, stirring, and obtaining a sol solution containing organic-inorganic hybrid hollow microspheres;

[0010] S3, immersing the fiber felt in the sol solution containing the organic-inorganic hybrid hollow microspheres, allowing it to stand, and drying it to obtain the composite aerogel felt.

[0011] In step S1, the silicon source is one or more of ethyl orthosilicate, dimethyldiethoxysilane, (3-aminopropyl)triethoxysilane and dimethyldichlorosilane.

[0012] The solvent is one or more of anhydrous ethanol, n-heptane and n-hexane.

[0013] Based on the mass of the silicon source, the amount of phytic acid used is 1-2%, preferably 1%.

[0014] The conditions of the hydrolysis reaction are: room temperature, and a time of 22-24 hours, preferably 24 hours.

[0015] The pH of the system is 1.9-2.1, preferably 2.

[0016] In step S2, based on the silicon source, the amount of the organic-inorganic hybrid hollow microspheres is 5-10%, preferably 6-7%.

[0017] In step S2, the organic-inorganic hybrid hollow microspheres are prepared according to the following method:

[0018] Under alkaline conditions, a silane coupling agent and a volatile solvent are added to water, ultrasonicated, condensed and refluxed, an initiator is added to initiate a free radical polymerization reaction, centrifuged, and washed to obtain organic-inorganic hybrid hollow microspheres;

[0019] Wherein: the alkaline condition is achieved by adding ammonia water to adjust the pH value, and the pH range is 9.8-10.2, preferably 10.0.

[0020] The silane coupling agent is 3-methacryloxypropyltrimethoxysilane.

[0021] The volatile solvent is isoamyl acetate.

[0022] The volume ratio of the silane coupling agent, the volatile solvent and the water is (6-7):(39-41):1, preferably 6.8:40:1.

[0023] The ultrasonic conditions are: power of 230-250 W, preferably 240 W, and time of 10-30 min, preferably 15-20 min.

[0024] The conditions for the condensation reflux are: under an inert atmosphere, a temperature of 68-72° C., preferably 70° C., and a time of 25-35 min, preferably 30 min.

[0025] The initiator is potassium persulfate.

[0026] Based on the mass of the silane coupling agent, the amount of the initiator is 4-5%, preferably 4.8%.

[0027] The conditions of the free radical polymerization reaction are: temperature of 65-75° C., preferably 70° C., and time of 10-18 h, preferably 12 h.

[0028] In step S3, the soaking conditions are: the temperature is room temperature, and the time is 22-24 hours, preferably 24 hours.

[0029] In a second aspect, the present invention further provides a composite aerogel felt containing organic-inorganic hybrid hollow microspheres obtained by the preparation method.

[0030] In a third aspect, the present invention further provides the use of the composite aerogel felt containing organic-inorganic hybrid hollow microspheres as a thermal insulation material in industrial pipelines (such as oil pipelines).

[0031] The beneficial effects achieved by the present invention are as follows:

[0032] 1. The present invention introduces phytic acid into the preparation of aerogel felt by normal pressure drying process. By utilizing the acidity and chelating property of phytic acid, on the one hand, phytic acid can participate in the reaction process of silica sol, which is beneficial to the formation of silicon-oxygen-silicon bonds and a small amount of phosphorus-oxygen-silicon network, thereby improving the stability of aerogel structure and thus improving the thermal insulation performance of aerogel felt material. On the other hand, phytic acid can promote the hydrolysis of silicon source, prompt the reaction of raw materials to be complete without powder falling, avoid the problems of multiple washing and complicated process in the existing preparation process, and simplify the process flow.

[0033] 2. The present invention further introduces organic-inorganic hybrid hollow microspheres in the preparation of aerogel felt by a normal pressure drying process. The organic-inorganic hybrid hollow microspheres are hollow particles formed by the accumulation of nano-silicon dioxide, with a cavity structure in the center. The accumulation can simulate the supercritical SiO2 aerogel structure and has good dispersibility in the silica sol system. It can maintain the microstructure of the aerogel during the rapid volatilization of the solvent and avoid agglomeration formation, thereby improving the thermal insulation performance of the composite aerogel felt.

[0034] 3. The method described in the present invention can also significantly increase the interfacial contact angle of the aerogel felt, thereby improving the hydrophobicity of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 A process flow chart for preparing a composite aerogel felt containing organic-inorganic hybrid hollow microspheres provided by the present invention.

[0036] Figure 2 This is a TEM image of the organic-inorganic hybrid hollow microspheres provided by the present invention.

[0037] Figure 3 The composite aerogel felt prepared in Example 1 31 P NMR solid state nuclear magnetic spectrum.

[0038] Figure 4 The composite aerogel felt prepared in Comparative Example 1 29 Si NMR spectrum.

[0039] Figure 5 Optical photographs of the composite aerogel felts prepared in Examples 1 and 2; (a) represents Example 1, and (b) represents Example 2.

[0040] Figure 6 This is an optical photograph of the aerogel felt prepared in Comparative Example 2. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0042] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0043] Unless otherwise specified, the reagents, materials, instruments, etc. used in the following examples can be obtained from commercial sources.

[0044] The organic-inorganic hybrid hollow microspheres used in the following examples were prepared according to the following operation:

[0045] Take 80 mL of water and put it in a 200 mL glass bottle, add ammonia water to the water to adjust the pH value to 10.0, add 0.4 mL of 3-isobutylacryloxypropyltrimethoxysilane and 1.2 mL of isoamyl acetate, ultrasonicate at room temperature, the ultrasonic power is 240 W, the ultrasonic time is 20 min, nitrogen is passed for 30 min, condense and reflux at 70 ° C, add 20 mg of potassium persulfate to initiate free radical polymerization, stop the reaction after 12 hours, centrifuge and wash the product to obtain organic-inorganic hybrid hollow microspheres.

[0046] Example 1: Preparation of composite aerogel felt in laboratory

[0047] like Figure 1 As shown, the steps are as follows:

[0048] (1) Weigh 13.3 g of ethyl orthosilicate and 7.1 g of dimethyldiethoxysilane into a 200 mL beaker, then add 120 mL of anhydrous ethanol, 3 mL of water and 2 mL of phytic acid aqueous solution (concentration is 0.1 g / mL) in sequence, stir and hydrolyze at room temperature for 24 h, then add 0.2 mL of ammonia aqueous solution (concentration is 1 M), at this time the pH of the system is 5.73, stir for 10 min, and obtain a silica sol solution.

[0049] (2) Add 1.22 g of organic-inorganic hybrid hollow microspheres (the amount of microspheres used is 6% of the amount of ethyl orthosilicate and dimethyldiethoxysilane used) to the obtained silica sol solution, and stir for 2 h to obtain a sol solution containing organic-inorganic hybrid hollow microspheres.

[0050] (3) The prepared fiber felt is placed in a sol solution containing organic-inorganic hybrid hollow microspheres and soaked and fully penetrated, taken out and allowed to stand for 24 hours, and dried at 60° C. to obtain a composite aerogel felt containing organic-inorganic hybrid hollow microspheres.

[0051] Example 2: Large-scale preparation of composite aerogel felt

[0052] Here are the steps:

[0053] (1) Weigh 6 kg of ethyl orthosilicate and 3.2 kg of dimethyldiethoxysilane and add them to a 100 L reactor, then add 60 L of anhydrous ethanol, 0.9 L of water and 930 mL of phytic acid aqueous solution (concentration is 0.1 g / mL) in sequence, stir and hydrolyze at room temperature for 24 h, add 100 mL of ammonia aqueous solution (concentration is 1 M), at this time the pH of the system is 5.81, stir for 30 min, and obtain a silica sol solution.

[0054] (2) 552 g of organic-inorganic hybrid hollow microspheres were added to the obtained silica sol solution and stirred for 2 h to obtain a sol solution containing organic-inorganic hybrid hollow microspheres.

[0055] (3) The prepared fiber felt is placed in the obtained sol solution containing organic-inorganic hybrid hollow microspheres to be completely immersed and penetrated, taken out and allowed to stand for 24 hours, and naturally dried to obtain a composite aerogel felt containing organic-inorganic hybrid hollow microspheres.

[0056] Comparative Example 1

[0057] The difference from Example 1 is that the phytic acid aqueous solution in Example 1 is replaced by a hydrochloric acid aqueous solution of the same concentration to obtain a composite aerogel felt containing organic-inorganic hybrid hollow microspheres.

[0058] Comparative Example 2 (without introduction of organic-inorganic hybrid hollow microspheres, equal amount of silicon source)

[0059] Here are the steps:

[0060] (1) Weigh 13.1 g of ethyl orthosilicate and 7 g of dimethyldiethoxysilane into a 200 mL beaker, then add 119 mL of anhydrous ethanol, 3 mL of water and 2 mL of phytic acid aqueous solution (concentration is 0.1 g / mL) in sequence, stir and hydrolyze for 24 h, then add 0.2 mL of ammonia aqueous solution (concentration is 1 M), at this time the pH of the system is 5.69, stir for 10 min, and obtain a silica sol solution.

[0061] (2) The prepared fiber felt is placed in the obtained silica sol solution and soaked and penetrated completely, taken out and allowed to stand for 24 hours, and dried at 60° C. to obtain a silica composite aerogel felt.

[0062] Effect verification:

[0063] 1. Structural characteristics of organic-inorganic hybrid hollow microspheres

[0064] like Figure 2 As shown, the size of the organic-inorganic hybrid hollow microsphere is submicron, the particle size distribution is uniform, and it has a cavity structure. The hollow microsphere is composed of a silicon-containing polymer, wherein the shell layer has an inorganic network of Si-O-Si and an organic segment part after double bond polymerization. The inorganic network and the organic segment are connected by chemical bonds, forming an organic-inorganic hybrid structure with amphiphilic and hydrophilic properties.

[0065] 2. Microstructure of composite aerogel felt

[0066] like Figure 3 It can be seen that a bridge structure (PO-Si) is formed between phosphorus and silicon in the material obtained in Example 1, while the reference phosphate material mainly exists in a POP structure; Figure 4 As shown, the material obtained in Comparative Example 1 does not contain any phosphorus, and it mainly exists in a silicate network structure (Si-O-Si). This shows that the present invention introduces phytic acid to participate in the reaction process of silica sol, promotes the formation of silicon-oxygen-silicon bonds and a small amount of phosphorus-oxygen-silicon network, thereby improving the stability of the aerogel structure and the thermal insulation performance of the aerogel felt material.

[0067] 3. Macrostructure of composite aerogel felt

[0068] like Figure 5 As shown, the structure of the composite aerogel felt prepared in Example 1 and Example 2 is relatively loose, such as Figure 6As shown, the structure of the aerogel felt obtained in Comparative Example 2 is relatively dense, which shows that the present invention can stabilize the network structure of the aerogel felt and avoid agglomeration by introducing organic-inorganic hybrid hollow microspheres, thereby making the material softer and having better thermal insulation properties, which is conducive to industrial use.

[0069] 4. Investigation of fan loss

[0070] The aerogel felts obtained in Example 1, Example 2 and Comparative Example 1 and Comparative Example 2 were manually folded, and the results are shown in the following table.

[0071] Table 1 Performance test of aerogel felt

[0072]

[0073]

[0074] It can be seen from Table 1 that under laboratory-scale preparation conditions, compared with the materials obtained in Comparative Examples 1 and 2, the material obtained in Example 1 has lower thermal conductivity, a larger interface contact angle, better hydrophobicity, and the obtained material does not shed powder and has better structural stability.

[0075] In large-scale production, compared with existing aerogel felt products, the material obtained in Example 2 has a lower thermal conductivity at a high temperature of 500°C, and can better play a role in heat preservation of high-temperature pipelines.

[0076] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a composite aerogel felt by drying at normal pressure, comprising the following steps: S1, adding a silicon source, a solvent, and phytic acid into water to carry out a hydrolysis reaction, and then adjusting the pH of the system to obtain a silica sol solution; S2, adding organic-inorganic hybrid hollow microspheres to the silica sol solution, stirring, and obtaining a sol solution containing organic-inorganic hybrid hollow microspheres; S3, immersing the fiber felt in the sol solution containing the organic-inorganic hybrid hollow microspheres, allowing it to stand, and drying it to obtain the composite aerogel felt.

2. The method according to claim 1, characterized in that: In step S1, the silicon source is one or more of ethyl orthosilicate, dimethyldiethoxysilane, (3-aminopropyl)triethoxysilane and dimethyldichlorosilane; The solvent is one or more of anhydrous ethanol, n-heptane and n-hexane; Based on the mass of the silicon source, the amount of phytic acid used is 1-2%.

3. The method according to claim 1 or 2, characterized in that: In step S1, the conditions of the hydrolysis reaction are: the temperature is room temperature, and the time is 22-24 hours.

4. The method according to any one of claims 1 to 3, characterized in that: In step S1, the pH of the system is 1.9-2.

1.

5. The method according to any one of claims 1 to 4, characterized in that: In step S2, based on the silica sol solution, the amount of the organic-inorganic hybrid hollow microspheres is 5-10%.

6. The method according to any one of claims 1 to 5, characterized in that: In step S2, the organic-inorganic hybrid hollow microspheres are prepared according to the following method: under alkaline conditions, a silane coupling agent and a volatile solvent are added to water, ultrasonicated, condensed and refluxed, an initiator is added to initiate a free radical polymerization reaction, centrifuged, and washed to obtain organic-inorganic hybrid hollow microspheres.

7. The method according to any one of claims 1 to 6, characterized in that: In step S3, the soaking and standing conditions are: the temperature is room temperature, and the time is 22-24 hours.

8. A composite aerogel felt containing organic-inorganic hybrid hollow microspheres obtained by the method according to any one of claims 1 to 7.

9. Use of the composite aerogel felt containing organic-inorganic hybrid hollow microspheres as claimed in claim 8 as a thermal insulation material in industrial pipelines.

10. The use according to claim 9, characterized in that: The industrial pipeline is a petroleum pipeline.

Citation Information

Patent Citations

  • Aerogel fibrofelt composite material and preparation method thereof

    CN116122042A

Cited By

  • Ultralow-thermal-conductivity silicon oxide aerogel heat insulation felt and preparation method thereof

    CN120817778A

  • An ultralow thermal conductivity silicon oxide aerogel insulation felt and a preparation method thereof

    CN120817778B